Acyl‐Chain Elongation Drives Ketosynthase Substrate Selectivity in trans‐Acyltransferase Polyketide Synthases1. Issue 6 (21st December 2014) - Jenner, Matthew; Afonso, José Pedro; Bailey, Hannah R.; Frank, Sarah; Kampa, Annette; Piel, Jörn; Oldham, Neil J.
Abstract: Type I modular polyketide synthases (PKSs), which are responsible for the biosynthesis of many biologically active agents, possess a ketosynthase (KS) domain within each module to catalyze chain elongation. Acylation of the KS active site Cys residue is followed by transfer to malonyl‐ACP to yield an extended β‐ketoacyl chain (ACP=acyl carrier protein). To date, the precise contribution of KS selectivity in controlling product fidelity has been unclear. Six KS domains from trans ‐acyltransferase (trans‐AT) PKSs were subjected to a mass spectrometry based elongation assay, and higher substrate selectivity was identified for the elongating step than in preceding acylation. A close correspondence between the observed KS selectivity and that predicted by phylogenetic analysis was seen. These findings provide insights into the mechanism of KS selectivity in this important group of PKSs, can serve as guidance for engineering, and show that targeted mutagenesis can be used to expand the repertoire of acceptable substrates. Abstract : Extension granted : In vitro studies on ketosynthase (KS) domains from trans ‐acyltransferase polyketide synthases were carried out by varying the substrate (R group) and measuring product formation by mass spectrometry. The results revealed substrate selectivity for the chain elongation step that mirrors the predictions based on phylogenetic analysis. Substrate tolerance profiles provide valuable information for the bioengineering of polyketide assembly lines.